Dreamscape and death : an analysis of three contemporary novels and a film - Truter, Victoria Zea (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2014)
With its focus on the relationship between dreamscape and death, this study examines the possibility of indirectly experiencing "“ through writing and dreaming "“ that which cannot be directly experienced, namely death. In considering this possibility, the thesis engages at length with Maurice Blanchot's argument that death, being irrevocably absent and therefore unknowable, is not open to presentation or representation. After explicating certain of this thinker's theories on the ambiguous nature of literary and oneiric representation, and on the forfeiture of subjective agency that occurs in the moments of writing and dreaming, the study turns to an examination of the manner in which such issues are dealt with in selected dreamscapes. With reference to David Malouf's An Imaginary Life, Alan Warner's These Demented Lands, Cormac McCarthy's The Road, and Richard Linklater's Waking Life, the thesis explores the literary and cinematic representation of human attempts to define, resist, or control death through dreaming and writing about it. Ultimately, the study concludes that such attempts are necessarily inconclusive, and that it is only ever possible to represent death as a (mis)representation.
Keywords: Malouf, David, 1934- -- Criticism and interpretation; Warner, Alan -- Criticism and interpretation; McCarthy, Cormac, 1933- -- Criticism and interpretation; Linklater, Richard, 1960- -- Criticism and interpretation; Australian fiction -- History and criticism; American fiction -- History and criticism; English fiction -- History and criticism; Motion pictures, American -- History and criticism; Malouf, David, 1934- An imaginary life; Warner, Alan -- These demented lands; McCarthy, Cormac, 1933- -- Road; Linklater, Richard, 1960- -- Waking Life; Death in literature